2018
DOI: 10.1590/2317-1782/20182016256
|View full text |Cite
|
Sign up to set email alerts
|

Intervenção guiada por videofeedback a famílias de crianças com deficiência auditiva

Abstract: In order to improve speech-language development in children with hearing impairment, in addition to speech-language therapy, the family should be the modifying agent for a satisfactory therapeutic response. Studies that analyze the effectiveness of speech-language pathology (SLP) intervention programs through video feedback are important, given the positive effects of this tool on the modification of behaviors with families of children with disabilities. Therefore, it is believed that video feedback interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 12 publications
1
14
0
13
Order By: Relevance
“…Different theoretical and methodological approaches to VFI are described in literature (e.g., Cohen and Beebe, 2002;Juffer et al, 2005Juffer et al, , 2017Schechter et al, 2006). Previous research has highlighted that VFI is associated with better child development and parent-child relationship in different clinical contexts, including children at risk for behavioral problems (Velderman et al, 2006;Balldin et al, 2018), preterm infants (Hoffenkamp et al, 2015;Barlow et al, 2016), hearing impairments (Santos and Brazorotto, 2018), maternal psychopathology (Rackett and Macdonald, 2014;Høivik et al, 2015;Kristensen et al, 2017), and ethnic minorities (Yagmur et al, 2014). Nonetheless, evidence on the effects of VFI in families of children with ND is sparse and lacks systematization.…”
Section: Introductionmentioning
confidence: 99%
“…Different theoretical and methodological approaches to VFI are described in literature (e.g., Cohen and Beebe, 2002;Juffer et al, 2005Juffer et al, , 2017Schechter et al, 2006). Previous research has highlighted that VFI is associated with better child development and parent-child relationship in different clinical contexts, including children at risk for behavioral problems (Velderman et al, 2006;Balldin et al, 2018), preterm infants (Hoffenkamp et al, 2015;Barlow et al, 2016), hearing impairments (Santos and Brazorotto, 2018), maternal psychopathology (Rackett and Macdonald, 2014;Høivik et al, 2015;Kristensen et al, 2017), and ethnic minorities (Yagmur et al, 2014). Nonetheless, evidence on the effects of VFI in families of children with ND is sparse and lacks systematization.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of significant reports regarding difficulties in family relationships as a result of HI (Figure 1) may have as a possible justification the way in which the diagnostic process is conducted by professionals from the Hearing Health Program in question, which reinforces the importance of assistance to hearing impaired and their family during the process of diagnosis and language monitoring of children with hearing Hearing impairment and family relationships impairment (3,8) . This finding was also presented in a recent study (1) , in which parents and family members did not report significant complaints associated with the relationship between children with HI and their families, as they consider that the diagnosis of HI, in itself, does not impact the relationship between the child development and family life.…”
Section: Discussionmentioning
confidence: 99%
“…Parents reported not having communication difficulties, regardless of the degree of hearing impairment (Table 1), possibly due to the positive change in communicative interactions after the intervention program between children with HI and their families (8,11,12) . It is worth noting that the family members who responded to the questionnaire have also participated, together with their children, in intervention sessions on hearing rehabilitation in the Hearing Health Program in question, as already mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed a large effect on the Emotional Availability (EA) scales for both the waiting-list and the intervention group (Lam-Cassettari et al, 2015), indicating that the video feedback intervention enhanced parental sensitivity and attentiveness toward their deaf and hard-of-hearing children. The only other published study that has used VIG with families of deaf and hard-of-hearing children is a non-randomized clinical trial with case reports (dos Santos and Brazorotto, 2018). This study found post-intervention improvements in parent-child interactions as measured by an observation scale looking at the use of facilitative language strategies by the parents such as being child-led and using an expansive vocabulary.…”
Section: Introductionmentioning
confidence: 97%